2017
DOI: 10.1111/eea.12579
|View full text |Cite
|
Sign up to set email alerts
|

Fitness‐related offspring sex allocation of Anastatus disparis, a gypsy moth egg parasitoid, on different‐sized host species

Abstract: Anastatus disparis (Ruschka) (Hymenoptera: Eupelmidae) is an egg parasitoid and considered a potential biological control agent of the gypsy moth, Lymantria dispar (L.) (Lepidoptera: Lymantriidae). Only male offspring of A. disparis emerge from single eggs of L. dispar in the laboratory, and A. disparis exhibits low parasitism on L. dispar in the field. We therefore selected several lepidopteran species with various body sizes to evaluate the optimal egg size for hosting A. disparis. In addition, we explored w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…It can develop three to four generations on L. dispar eggs annually in Northern China (Yao and Yan 1994). In our previous research, we found that the offspring of A. disparis reared on egg masses of gypsy moth were male-biased and small-bodied (Liu et al 2017). However, when they were reared on a larger host, Antheraea pernyi Guerin-Meneville (Lepidoptera: Saturnidae), the offspring were female-biased and had a larger body size compared with those reared from gypsy moth (Liu et al 2017).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It can develop three to four generations on L. dispar eggs annually in Northern China (Yao and Yan 1994). In our previous research, we found that the offspring of A. disparis reared on egg masses of gypsy moth were male-biased and small-bodied (Liu et al 2017). However, when they were reared on a larger host, Antheraea pernyi Guerin-Meneville (Lepidoptera: Saturnidae), the offspring were female-biased and had a larger body size compared with those reared from gypsy moth (Liu et al 2017).…”
Section: Introductionmentioning
confidence: 91%
“…Anastatus disparis Ruschka (Hymenoptera: Eupelmidae) is a solitary egg parasitoid of several noxious lepidopteran forest pests, including the gypsy moth, Lymantria dispar (L.) (Lepidoptera: Lymantriidae) (Crossman 1925, Kurir 1944, Yan et al 1989, Li and Lou 1992, Alalouni et al 2013, Liu et al, 2017. It can develop three to four generations on L. dispar eggs annually in Northern China (Yao and Yan 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual dimorphisms related to behaviour, physiology, and morphology in A. disparis have been extensively described. First, although wasp body size is correlated with host quality [44] [46], the body size of females is typically significantly larger than males. Females can live more than one month in the field and lay hundreds of eggs over their lifetime, while males live for only approximately 5-7 days and exhibit frequent and extreme fighting behaviour to acquire mating opportunities [43][46] [47].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dimorphisms related to behaviour, physiology, and morphology in A. disparis have been extensively described. First, although wasp body size is correlated with host quality [41] [43], the body size of females is always significantly larger than that of males. Second, females can live more than one month in the field and lay hundreds of eggs over their lifetime, while males live for only approximately 5-7 days and exhibit frequent and extreme fighting behaviour to acquire mating opportunities [40][43] [44].…”
Section: Introductionmentioning
confidence: 99%